THE PREDICATE IN THE MACEDONIAN LANGUAGE-TEACHING CURRICULUM ANDTEXTBOOKS IN THE PRIMARY AND SECONDARY SCHOOL IN THE RM - Janusheva, Violeta (Philological Studies, 2019)
The predicate is a constitutive part of the sentence and, as such, it is critical for successful syntactic analysis of sentences. Taking into account everyday practice of higher education, it is clear that students have difficulties determining the predicate in sentences. The goal of this paper is clear, it is to examine the causes for the widespread insufficient competency to determine the predicate in sentences in students of higher education. The research has a qualitative paradigm (content analysis). It analyses the Macedonian language-teaching curriculum and textbooks (sample) regarding the predicate in the primary and secondary education in the Republic of Macedonia. It also has a quantitative paradigm, fot it analyses the thoughts and attitudes of 200 students (from all the regions in Macedonia) (sample) which attend the courses of Modern Macedonian language and courses of the Syntax of the Macedonian language in the Faculty of Education in Bitola. The methods for processing the data and gaining conclusions are analysis, comparison and synthesis. The results show that the Macedonian language curriculum and textbooks are the causes for the students’ insufficient competencies to determine the predicate in a given sentence. The concepts of simple and complex verb predicates and simple and complex predicates that require complement are introduced too late, in the third year of the secondary education (vocational and gymnasium), and they are often explained incorrectly. These finding are confirmed by the survey of students, which shows that most of the students cannot determine the predicate in the sentence, and this refers especially to the complex predicates that require complement. Therefore, students cannot make correct syntactic analysis of sentences. According to the students, the elementary and secondary school’s teachers pay a great attention to literature and neglect grammar.